Schizophrenia: recent advances in LC–MS/MS methods to determine antipsychotic drugs in biological samples. (21st January 2019) - Costa Queiroz, Maria Eugênia; Lemos Pinto, Mônia Aparecida; Carneiro Cruz, Jonas; Mayumi Ushirohira, Juliana; da Silva Dias, Isabella Caroline; Cecilio Hallak, Jaime E
Schizophrenia is one of the most debilitating and costly illnesses worldwide. First-generation antipsychotics such as chlorpromazine and haloperidol succeeded in controlling the positive symptoms of schizophrenia, but had significant extrapyramidal effects that led to the search for new agents and the release of second-generation (or atypical) antipsychotics. These drugs had a lower risk of adverse motor symptoms. Therapeutic drug monitoring has become a useful tool to optimize schizophrenia treatment and HPLC–MS/MS has been considered the primary technique to monitor antipsychotics. This review comprises three sections: schizophrenia pathophysiology and treatment; recent advances in LC–MS/MS methods designed to measure levels of antipsychotics and their metabolites in plasma samples (selectivity, matrix effect and sensitivity); and the importance of therapeutic drug monitoring.